2007
DOI: 10.1002/jbm.b.31020
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of a self‐etching system to dental substrate prepared by Er:YAG laser or air abrasion

Abstract: The purpose of this study was to assess the microtensile bond strength of a self-etching adhesive system to enamel and dentin prepared by Er:YAG laser irradiation or air abrasion, as well as to evaluate the adhesive interfaces by scanning electron microscopy (SEM). For microtensile bond strength test, 80 third molars were randomly assigned to five groups: Group I, carbide bur, control (CB); II, air abrasion with standard tip (ST); III, air abrasion with supersonic tip (SP); IV, Er:YAG laser 250 mJ/4 Hz (L250);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0
8

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 52 publications
4
47
0
8
Order By: Relevance
“…12,18 Such approaches replace the invasive technique of using highspeed dental burs. 12,17,19 , Cavity preparation using lasers takes more time than cavity preparation with rotary cutting instruments, but advantages include low noise and vibration and eliminating the need for local anesthesia in most cases. An additional advantage of laser cavity preparation is that a smear layer of debris is not produced on the surface of the prepared cavity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,18 Such approaches replace the invasive technique of using highspeed dental burs. 12,17,19 , Cavity preparation using lasers takes more time than cavity preparation with rotary cutting instruments, but advantages include low noise and vibration and eliminating the need for local anesthesia in most cases. An additional advantage of laser cavity preparation is that a smear layer of debris is not produced on the surface of the prepared cavity.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In hydrophilic monomers, carboxylic and phosphate groups act as proton donors in the partial demineralization of the smear layer and have the potential to bond ionically with the calcium from residual hydroxyapatite. 7 The current trend in minimally invasive dentistry involves alternative techniques for dental cavity preparation, such as laser irradiation [11][12][13][14][15][16][17] and aluminum oxide air abrasive. 12,18 Such approaches replace the invasive technique of using highspeed dental burs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The lower bond strength values obtained with the association of the total-etch adhesive tested with the laser preparation may also be due to the fact that irradiation of dentin with Er:YAG laser can denature the organic components of subsurface intertubular dentin, and affect the surface morphology and chemistry of dentin, mainly the organic components, 28,29 which may not be favorable for bonding. 21,30 In addition, the remaining denatured collagen fibrils are fused together, thus, the resin diffusion into the interfibrillar collagen spaces is probably prevented, compromising the bonding effectiveness. 24 The association of Adper Scotchbond SE with CVD tips produced lower means than when dentin was prepared with diamond burs or laser, in spite of the low thickness smear layer formed by this method of dentin preparation and the high aggressiveness of this adhesive system.…”
Section: 17mentioning
confidence: 99%
“…Some studies have shown that even after etching by an acid or self-etching agent, the bond strength of irradiated permanent and deciduous dentin is lower than that of regular acid-etched dentin [8][9][10]. However, different results have been found in other studies, making this a controversial issue [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%